A comparison of two common sample preparation techniques for lipid and fatty acid analysis in three different coral morphotypes reveals quantitative and qualitative differences - Jessica A. Conlan; Melissa M. Rocker; David S. Francis (PeerJ, 2017)
Lipids are involved in a host of biochemical and physiological processes in corals. Therefore, changes in lipid composition reflect changes in the ecology, nutrition, and health of corals. As such, accurate lipid extraction, quantification, and identification is critical to obtain comprehensive insight into a coral’s condition. However, discrepancies exist in sample preparation methodology globally, and it is currently unknown whether these techniques generate analogous results. This study compared the two most common sample preparation techniques for lipid analysis in corals: (1) tissue isolation by air-spraying and (2) crushing the coral in toto. Samples derived from each preparation technique were subsequently analysed to quantify lipids and their constituent classes and fatty acids in four common, scleractinian coral species representing three distinct morphotypes (Acropora millepora, Montipora crassotuberculata, Porites cylindrica, and Pocillopora damicornis). Results revealed substantial amounts of organic material, including lipids, retained in the skeletons of all species following air-spraying, causing a marked underestimation of total lipid concentration using this method. Moreover, lipid class and fatty acid compositions between the denuded skeleton and sprayed tissue were substantially different. In particular, the majority of the total triacylglycerol and total fatty acid concentrations were retained in the skeleton (55–69% and 56–64%, respectively). As such, the isolated, sprayed tissue cannot serve as a reliable proxy for lipid quantification or identification in the coral holobiont. The in toto crushing method is therefore recommended for coral sample preparation prior to lipid analysis to capture the lipid profile of the entire holobiont, permitting accurate diagnoses of coral condition.